Overseeing health care facilities in Shanghai, China: regulatory regime, activities and challenges of the governmental regulatory system - Yizhong Zhou; Zechang Lu; Zhifeng Yang; Huidi Li; Yingyao Chen (BMC, 2019)
Abstract Background Government regulation has played a crucial role in ensuring the quality, safety and equity of health care. However, few empirical studies have investigated Chinese governmental oversight of health care facilities in terms of regulatory arrangements and approaches. This study aims to explore the regulatory regime and main activities within the health sector in Shanghai, a city featuring abundant health care resources and a complex medical system, to provide policy implications for better regulation and offer valuable reference for elsewhere in China and other developing countries. Methods We explored the structure and main activities of government regulation over health care facilities in Shanghai, compared it with the regulatory system in Hong Kong and Taipei through a literature review and analyzed the data on regulatory activities conducted by the local Health Supervision Agencies using descriptive statistical analysis. The data were collected from the Shanghai Statistical Yearbook 2014-2018 and the centralized data bank of the Shanghai Health Supervision Authority. Results Shanghai has established a unique governmental regulatory system compared to Hong Kong and Taipei. We found health care facilities in Shanghai underwent less frequent inspections between 2013 and 2017, as average annual inspections at individual facilities decreased from 3.8 to 2.7. The number of annual administrative penalties and notifications issued for accumulating points on local health care facilities' violations decreased by 24.8 and 40.7%, respectively, and complaints against health care facilities decreased by 29.1% during the study period. Conclusions The local governmental regulatory system played a vital role in overseeing the health care facilities and ensuring their legal compliance by exerting the various regulatory activities. Both annual administrative penalties and notifications of accumulating points on local health care facilities' violations decreased considerably, with complaints against health care facilities reducing. As our study identified significant challenges, including regulatory fragmentation and no risk-based approach used, we offer recommendations to develop new policies and establish new mechanisms for better regulation.